Improvement of DAS-28 ESR score in Egyptian children and adolescents with juvenile idiopathic arthritis treated with etanercept - Rasha Abdel-Raouf Afifi; Heba Taher Osman; Walaa Aboulkasem Shahin; Menna-t-allah Alaa ElDin Yousef (Egyptian Pediatric Association Gazette, 2017)
Aim of study: To assess the efficacy and safety of using anti-tumor necrosis factor-α (TNF-α), Etanercept (ETN) in treatment of children and adolescents with Juvenile Idiopathic arthritis (JIA). Patients and methods: This retrospective cohort study included 18 children and adolescents who were diagnosed as JIA and treated with anti-tumor necrosis factor-α (TNF-α), ETN for at least 6 months due to failure of synthetic disease-modifying antirheumatic drugs (sDMARDS) as methotrexate (MTX). Before starting ETN treatment, all patients were receiving MTX in addition to non-steroidal anti-inflammatory drugs (NSAIDs). Other medications used were Prednisolone, Leflunamide and Hydroxychloroquine. As per recommendations of the European League Against Rheumatism (EULAR), failure of these DMARDs is an indication to start biological DMARDs. Anti TNF-α, mainly ETN is one of the most commonly used biological DMARDs in treating JIA. Clinical scoring using DAS28-ESR score was done for all patients at time of enrollment, 3 months and 6 months after starting ETN. The effect of different clinical and laboratory variables on the outcome of ETN treatment was assessed. Results: There was statistically significant improvement in DAS28-ESR after 3 months of treatment (p = 0.001) and after 6 months (p = 0.049). There was no statistically significant difference in DAS-28 score between males and females, patients younger than 10 years and patients older than 10 years, neither at onset nor at 6 months’ follow up. Similarly, the duration of illness before starting ETN did not affect DAS28 score at 6 months of treatment. Conclusion: ETN treatment of JIA children and adolescents demonstrated safety and efficacy in clinical improvement of DAS28-ESR score at 3 and 6 months of treatment. However, further studies on a bigger number of patients, longer duration and using different biological agents are needed.